If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(r-1)=2(r-4)-5
We move all terms to the left:
5(r-1)-(2(r-4)-5)=0
We multiply parentheses
5r-(2(r-4)-5)-5=0
We calculate terms in parentheses: -(2(r-4)-5), so:We get rid of parentheses
2(r-4)-5
We multiply parentheses
2r-8-5
We add all the numbers together, and all the variables
2r-13
Back to the equation:
-(2r-13)
5r-2r+13-5=0
We add all the numbers together, and all the variables
3r+8=0
We move all terms containing r to the left, all other terms to the right
3r=-8
r=-8/3
r=-2+2/3
| 8(-3.5y-4)+(7y+5)=0 | | 380.96=190+0.88x | | x/2-9=3x-14 | | -3/8m+1-13/8=5 | | (3x-5)+2(7-5x)=0 | | -4x+10=x+45 | | 8x+50=100 | | 6+8y=22 | | 6(5y+6)=2y+8 | | 6x+20=35 | | 10c-(9-c)=86 | | 6x=1680 | | 8c+14=-6c+12 | | (2x+50)=3x | | -4.3(6.3x+-4.18)=58.56 | | 2x=1680 | | 18x-5-7x-13=25 | | 3x+-4=-1 | | 3(y+7)=4y-6 | | 0.75q^2=108 | | (X-2)=6x | | -10(8x-4)=-4(6+12x) | | -9(-9x-8)=-8x-17 | | 8x-32=56+6x | | 8q^2-23q-3=0 | | -9(-9x-8=-8x-17 | | -21=2x-(7-13) | | 7x-24+5x+14=13 | | 3+8x=3(2x)- | | 5n=100* | | 5(7k-3)=-8k-15 | | x2 –4x–5=0 |